The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.52218/ijbtob.v2i4.211
|View full text |Cite
|
Sign up to set email alerts
|

Management innovation, green product innovation, green process innovation influence on financial performance. A study of South African manufacturing firms.

Abstract: This research aims to evaluate the nexus of green innovation on registered companies' financial performance on the Johannesburg Stock Exchange (J.S.E.). The paper followed the content analysis approach in evaluating green products, green processes, management innovation ability, and green image variables on 64 manufacturing firms from 2011 up to 2018. This article adopted Smart PLS-SEM 3 analyses to check the models suggested for the study empirically. The findings reveal that management innovation ability had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…AS produced in table 5, leadership had an inverse moderating connection on the affiliation between CSR and GRNI. In the work of (Nsiah et al, 2022) research work in South Africa, their findings shows that management had a favorable effect on GRNI leading to a significant financial efficiency. The results have revealed that ENVL in the SME's sector do not participate in CSR activities that will lead to GRNI.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AS produced in table 5, leadership had an inverse moderating connection on the affiliation between CSR and GRNI. In the work of (Nsiah et al, 2022) research work in South Africa, their findings shows that management had a favorable effect on GRNI leading to a significant financial efficiency. The results have revealed that ENVL in the SME's sector do not participate in CSR activities that will lead to GRNI.…”
Section: Discussionmentioning
confidence: 96%
“…According to (Hernández-Linares et al, 2021), businesses committed to sustainable practices have a significant opportunity to attract additional customers. (Nsiah et al, 2022) research on management innovation and enterprise efficiency demonstrated that to achieve environmentally progress firms must integrate products and services that are green. Enterprises that disclose their corporate social responsibility are able to stay out of negative news.…”
Section: Literature Review Theoretical Synopsis Green Theory and Gree...mentioning
confidence: 99%
“…On specific notes, the management ensures that the hotel uses materials that produce minimal environmental problems, always search for and adopt materials that consume less energy and resources, use facilities that are easy to recycle, reuse, and decompose, and also uses items that helps to design or deliver environment friendly product or services. These were also supported by Green product, process, technology, and organisational innovation have a beneficial impact on sustainability performance (Elzek et al, 2021;Nsiah et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Frare and Beuren (2021) investigates 81 Brazilian agricultural technology companies, and emphasized the significance of green process innovation in promoting green entrepreneurship, proactive sustainability strategy and environmental performance. A survey of 64 South African firms showed that management innovation capability significantly influenced the green process in a positive way, while the relationship with financial performance was negligible (Nsiah et al, 2022). Saudi et al (2019) researched on SMEs in Malaysia, and found that while green product innovation and green process innovation have a favourable and significant impact on economic and environmental performance.…”
Section: Review Of Empirical Studies and Hypotheses Developmentmentioning
confidence: 99%